Circulation, Writing, and Rhetoric - Brooke, Collin Gifford; Gries, Laurie E. (Book collections on Project MUSE., 2018)
"It has been understood that writers quote, imitate, forward, borrow, dispute, engage with, and transform texts written by others. Contributors identify circulation as a threshold concept of Western literacy theory and explore five key themes concerning circulation: public rhetorics, feminism, new materialism, theories of delivery, and technologies"--Provided by publisher.